Seeds of transformation: Behavioral strategies to boost access and use of quality seeds - Hakizimana, Benadette; Ntawuyankira, Neilla; Ndabashinze, Blaise; Nchanji, Eileen (2024)
Beans are classified among the top subsistence crops in Burundi. They are a staple food present in almost every meal and provide 20% of calories and 50% of proteins. The majority of bean value chain actors in Burundi are women. Unfortunately, they are frequently disadvantaged by gender norms that deny them critical opportunities of empowerment such as decision-making, land ownership, and control over personal decisions. This, in interaction with climate challenges, contribute to slow down economic growth and development. To address the persistent challenge of limited access to quality agricultural inputs, particularly high-quality seeds, a social and behavioral strategy was developed under the CGIAR Seed Equal Initiative activities under work package 6. A workshop of seed producers, seed regulatory authorities, vulgarization officers was organized in Gitega to address the challenges in the bean value chain and promote equitable access to quality seeds through a comprehensive approach involving using multiple communication pathways, capacity building, social mobilization, policy advocacy, and gender-sensitive strategies. Strategies to increase access and use of quality seed was also developed in breakout sessions with participants.